2011
DOI: 10.1002/ange.201101317
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Fluorescent Probe for Vicinal‐Dithiol‐Containing Proteins and In Situ Imaging in Living Cells

Abstract: Direkter Ansatz: Bei einem schnellen und spezifischen Nachweis für Proteine mit vicinalen Dithiolgruppen (VDPs) ermöglicht eine Fluoreszenzsonde (siehe Bild) eine direkte Fluoreszenzanalyse. In diesem Ansatz gelingt durch Fluoreszenzpolarisation, Elektrophorese und direkte Bildgebung von VDPs deren nichtinvasive Verfolgung in vitro und in lebenden Zellen. Ferner erhält man einen Einblick in ihre mögliche Bedeutung für Zellfunktionen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…1 – 3 ). During colocalization studies with ER and lysosome trackers, some localisation within the ER was also observed 23 . Additionally, MitoESq-635 is widely compatible with different cell lines, such as HeLa, MCF7, RAW 264.7, U2OS and primary neuron cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1 – 3 ). During colocalization studies with ER and lysosome trackers, some localisation within the ER was also observed 23 . Additionally, MitoESq-635 is widely compatible with different cell lines, such as HeLa, MCF7, RAW 264.7, U2OS and primary neuron cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The synthesis of the target compound 5 is illustrated in Scheme 1. We first commenced the synthesis of compound 2 following the previously reported procedure with a slight modification [24,25] . Briefly, the protection reaction of commercially purchased 6-aminohexanoic acid ( 1 ) with di- tert -butyl dicarbonate (Boc 2 O) in the presence of sodium hydroxide quantitatively provided compound 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on excited-state intramolecular proton transfer (ESIPT), elegant ratiometric probes were reported. 30,31 Yet, their disadvantage is the low-fluorescence quantum yield of ESIPT-type fluorophores. The limitations of the existing approaches for ratiometric probes prompted us to develop alternative design principles.…”
Section: Introductionmentioning
confidence: 99%